SUPERCARRIERS : Naval air power in action - Holmes, Tony; Montbazet, Jean-Pierre (Osprey Publishing Limited, 1990)
A colorful, pictorial look at life aboard modern carriers. Live action photography of aircraft like the Hornet, Tomcat, and Sea Harrier includes images of the aircraft flying into combat against Iraq during "Operation Southern Watch" -- the only civilian photos taken of the event. In addition, there are images of crewmembers working atop the decks and servicing the aircraft. Firsthand accounts from pilots who take off and land on carrier decks, as well as from the men and women who work aboard these floating cities, are accompanied by full appendices providing histories of each unit featured